Reação de genótipos de soja transgênicos e convencionais a podridão branca da haste - Caires, Anderson Monteiro (2011)
Stem white rot, caused by Sclerotinia sclerotiorum, is increasing in soybean fields, mainly due to the use of seeds infected with the mycelium of the fungus. The control of soybean white mold requires the integration of various measures, including genetic control through the selection of soybean genotypes with partial resistance to the pathogen. The objective of this study was to evaluate the performance of transgenic and conventional soybean genotypes against the pathogen S. sclerotiorum, causal agent of stem white rot. The work was divided in two trials in field conditions to determine the method of inoculation. The first experiment evaluated partial resistance of conventional soybean genotypes of semi-early and medium/late cycles, by the inoculation of PDA disk, containing mycelium of the fungus, on the young stem of the plant. The second study evaluated the partial resistance of transgenic genotypes of early and medium/late cycles, by natural inoculation of the pathogen. The experimental design in both experiments was a randomized block with four replications. Results from the first experiment demonstrated varietal differences among genotypes of semi-early and medium/medium late cycles for the severity of stem white rot. Conventional genotypes GOBR03-2776-316 and Emgopa 4SFGO and transgenic genotypes BRY08-1.812Y, BRY08-1.018Y and GO.04 B2GO-5014 were selected as the resistance standard for future work. As susceptibility standards were selected genotypes conventional GOBR03-34GO-3151 and 1252-23 GOBR01-GO2 and transgenic genotypes BR05-20023-73615Y and BRBIGO03-30GO.